Prevalence and Risk Factors of Osteoporosis in Men with Chronic Obstructive Pulmonary Disease in Kars Province - Fatih Bağcıer; Gökhan Perinçek (Galenos Yayinevi, 2019)
Objective:Chronic obstructive pulmonary disease (COPD) is an important cause of morbidity and mortality today. Osteoporosis is known to be seen more commonly in COPD patients. This study aimed to evaluate the prevalence and risk factors of osteoporosis in men with COPD in Kars province.Materials and Methods:In this retrospective study performed on 88 male patients diagnosed with COPD, demographic data of the patients were recorded. The histories that duration of smoking and the use of steroid were documented. Pulmonary function tests and bone mineral densities were analyzed from their files.Results:The prevalence of osteopenia and osteoporosis in our study was 46.5% and 50%, respectively. The patient's age, smoking duration, COPD stage, and use of steroid history was significantly associated with osteoporosis (p<0.05). This relationship could not be demonstrated in the body mass index.Conclusion:The advanced stage of the disease, smoking, and the use of steroid should be a stimulant for osteoporosis in COPD patients. Early diagnosis and treatment are important in terms of protection from possible vital complications, especially fractures.